Indicators of severe prognosis of scrub typhus: prognostic factors of scrub typhus severity - Kim, Hyun Lee (BMC Infect Dis, 2019)
BACKGROUND: Scrub typhus is an acute disease, characterized by symptoms of fever, which occurs due to infection by Orientia tsutsugamushi. In most cases, patients recover from the disease with appropriate treatment, but serious and fatal complications may occur. The present study examined laboratory findings and tumor necrosis factor-alpha (TNF-α) levels of scrub typhus patients to identify the prognostic predictors of disease severity. METHOD: Patients whose scrub typhus diagnosis was confirmed by elevated indirect fluorescent antibody (IFA) levels and positive polymerase chain reaction (PCR) results were classified according to disease severity into one of three groups; i.e., deceased (n = 7), severe (n = 15), and mild (n = 15) retrospectively registered. Additionally, the usefulness of modified Acute Physiology and Chronic Health Evaluation II (APACHE II) score, C-reactive protein (CRP) level, white blood cell (WBC) count, and TNF-α level as prognostic predictors were examined. RESULT: The mean TNF-α levels of the deceased, severe, and mild groups were 53.5 (range: 7.8–147.8), 26.0 (1.7–64.4), and 8.8 pg/mL (4.6–16.0), respectively. The results of Kruskal-Wallis tests showed statistically significant differences between the deceased and severe groups versus the mild group (p = 0.005). CRP level and Modified APACHE II score also differed significantly among the groups (p = 0.046 and 0.007, respectively); however, WBC count did not (p = 0.196). CONCLUSION: An elevated serum TNF-α level in patients with scrub typhus could predict a severe condition or death and may be useful in predicting patient prognosis.